BIOLOGY OF Pentalonia nigronervosa COQUEREL ON VARIOUS ZINGIBERACEOUS CROPS - Rizki Anwar Efendi; Suparman SHK; Harman Hamidson (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Pentalonia nigronervosa Coquerel (Hemiptera; Aphididae) is the main vector of banana bunchy top disease caused by Banana Bunchy Top Virus (BBTV). The disease is an important and most damaging disease to the crop because infected bananas fail to produce fruits. As the vector of BBTV, P. nigronervosa is able to lives not only on banana plants but also on others plants, especially those belong to Family Zingiberaceae. The objective of this research was to reveal the biology of P. nigronervosa on banana and other plant species belong to Family Zingiberaceae commonly found around banana cultivation areas. The research was conducted in the Laboratory of Entomology, Department of Plant Protection, Faculty of Agriculture, Sriwijaya University from June to December 2021. The research was an experimental research arranged in a Completely Randomized Design using plant species as treatment and was replicated 10 times of replications. Young suckers of banana and zingiberaceous plants were used to rear the banana aphid where all biological aspects of the aphid were observed. P. nigronervosa and the young suckers were placed in a transparent pot covered with transparent plastic with a window made from cheese cloth to facilitate air movement. Room temperature was set to approximately 25oC since the aphid grow and reproduce well under such temperature. The results showed that P. nigronervosa are able to live and reproduce not only on banana but also on seven species of Zingiberaceous plants with little variation of some morphological and biological parameters. The significant different was found between biological characteristics of the aphid lived on torch ginger and cardamom which had longer life cycle but smaller fecundity compared to other experimental hosts used in the research.